Analysis of Online Learning Design in Elementary School - Rieza Trihatmoko Sandhy Surya; Tri Linggo Wati (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to describe the form of online learning design during the pandemic at Anggaswangi 1 State Elementary School. This study is a qualitative research with source triangulation research methods. The subjects in this study were the homeroom teacher of class V, grade 5 students and the Principal of the Anggaswangi State Elementary School 1. The data was collected by means of observation, interviews and documentation. The results of the study showed that at the beginning of online learning students were enthusiastic but teachers and schools were still groping in the delivery of learning materials so that they could be maximized. As time goes by, schools, teachers and students are ready for online learning, this is evidenced by the existence of facilities that support the implementation of online learning at Anggaswangi 1 State Elementary School, but students are starting to get bored in the implementation of their learning.